Family Ownership and Post-IPO Performance: Evidence in Malaysia - Risa , Kartika (2012)
This study constructs an analysis between family and non-family owned companies that were listed on the Bursa Malaysia during the period 2005 to 2008. In particular,this study investigates post-IPO performance of family ownership and impact on ownership structure and board composition using a comprehensive hand collected sample of 121 Malaysian IPOs. The descriptive statistics show that in the post-IPO period,the performance of family companies do not exhibit better performance compared to non-family companies. Meanwhile,the multivariate analysis suggests that board’s composition and ownership in companies influence the future performance after the companies going public. Moreover,for the elements of family characteristics, only percentage of family members on board that has weight on performance of Malaysian IPO companies following the listing. Overall,the evidence in this study supports the previous literatures on studies involving in performance of family and non-family company following the public offerings. These findings have implications for investors to support them in deciding the investment on the companies that have a concentrated structure of ownership. Moreover, from company viewpoint, overview of family business after going public can be used in developing tactics to forecast its future performance.